Discovery of COVID-19 protein inhibitors in phenolic acids of azadirachta indica (neem) using docking and pharmacokinetics - Roney, Miah; Huq, AKM Moyeenul; Mohd Fadhlizil Fasihi, Mohd Aluwi (Thammasat University, 2024)
COVID-19, a viral infection caused by the coronavirus SARS-CoV-2, is one of the world's most challenging diseases to cure. The fact that COVID-19 does not currently have any pharmaceutical treatments means that a concentrated effort must be made to discover the muchneeded remedies for this illness. The most attractive antiviral targets of SARS-CoV-2 are the spike protein and main protease (Mpro). In this work, sixteen phenolic acids of Azadirachta indica were docked into the active site of the spike protein and Mpro. The resulting compounds were then subjected to pharmacokinetic studies to establish the lead compounds. Based on the results, ferulic acid was found to be a promising candidate for further research into its potential as a SARS-CoV-2 inhibitor due to its positive anticipated pharmacokinetics and pharmacological properties.